Habilidades auditivas, potencial evocado auditivo e dominância hemisférica cerebral para habilidades cognitivas em músicos e cantores de dueto - Speranca, Simone [UNIFESP] (2019)
Objective. Verify and compare the auditory behaviors of recognition of dichotic syllables, temporal ordering of short and successive sounds that differ in terms of sound frequency, and measurements of brainstem auditory evoked potentials and Frequency Following Response, and correlate hemispheric domination brain for cognitive abilities, instrumental musicians, duet singers and non-musicians. Method. 39 otologically normalindividualsgrouped in 16 duet singers, 10 musicians, and 13 non-musicians were included in the analysis. Individuals with mental disorders, neurological or genetic syndromes and metabolic diseases were excluded. The study procedures were: evaluation of cerebral hemispheric dominance for cognitive abilities, and Syllables Dichotic Test (SDT), Pitch Pattern Test (PPT), Auditory Brainstem Response (ABR) and Frequency Following Response (FFR) .Result. Advantage of the right ear was observed in all groups in dichotic listening with syllables. As for the PPT the best performance in the task of naming occurred in the group of singing musicians, followed by the instrumentalist musicians, and after the non-musicians. Regarding humming, the best performance occurred in the group of instrumentalist musicians. ABR measures on the comparison between the ears, within each group, the groups of instrumentalist and non-musicians were similar. It is important to highlight that the duet singer musicians presented significant and minor values of the latency of the waveV and of the interpeakIII-Vof the right ear in relation to the left, and also presented higher values of the latency of the interpeak I-III of the right ear when compared to the group of non-musicians with statistical significance. In FFR, there was anincreased variation in the presence and absence of the waves for musicians groupsin relation to non-musicians, however there was no statistical significance. In terms of cerebral hemispheric dominance for cognitive abilities, for the musicians was the right hemisphere and for non-musicians it was Linear Hemispheric Integration. Conclusion. In the SDT, in the comparison between the groups the performance was similar between musicians and non-musicians. It stands out in relation to the values observed in the SDT that in the group of musicians there was better performance of the duet singers in relation to the instrumentalists. In relation to the advantage of the right ear, a similar performance was verified between the groups. In PPT the performance of music players exceeds those of non-musicians. It is important to observe that the duet singer musicians perform is better in the naming task while the instrumental musicians outperform is better inthe humming job, without statistical significance. In the ABR there was an increase in the latencies of the interpics I-III, transmission of the electrical impulse to the cochlear nucleus in the cerebral bridge, in the right ear in the duet singers in relation to the others. In the comparison of the left ear with the right ear in the group of duet singers, there was an increase in latency in the left ear of the interpic III-V and the latency of the V wave, which may indicate a compromise of the bridge in the brainstem. In the FFR there was greater robustness in the musicians, that is, tracings with better reproducibility and homogeneous thickness of the line. The dominance of the right hemisphere was verified for cognitive abilities in professional musicians and in the left hemisphere for non-musicians.